Test-Retest Reliability of the Speech, Spatial and Qualities of Hearing Scale (SSQ) in Brazilian Portuguese - Aguiar,Raiza Gorbachev Ribeiro (2019)
Abstract Introduction The Speech, Spatial and Qualities of Hearing Scale (SSQ) is a questionnaire designed to assess the auditory experience and quantify hearing disabilities in realistic communication situations, with particular attention to binaural hearing. Objective To determine the test-retest reliability of the SSQ in Brazilian Portuguese. Method A total of 35 individuals with mean age of 61 years and mean education of 7 years were interviewed. Themean auditory threshold was 44.29 dBNA in the best ear and 58.04 dBNA in theworst ear. The SSQ in Portuguesewas applied at two time points, test and retest. An interval of 7 to 20 days between interviews was established. The level of significance adopted was 0.05, or 5%. Results The analysis revealed a high Cronbach α coefficient for the three domains and for the general component of the scale, demonstrating good internal consistency between the items. In addition, a significant strong correlation was detected between test and retest of the SSQ on the analysis by domain and for the general component of the scale. A significant moderate-to-strong correlation between test and retest by question was found, except for question 2 of Part I. Conclusion The test-retest reliability indicators showed good stability of the Portuguese version of the SSQ, indicating that the scale is suitable for use in the hearingimpaired population in Brazil.